SCOLECITE: AS AN EFFICIENT AND REUSABLE CATALYST FOR THE SYNTHESIS O 2-AMINO- 4H-CHROMENES - LS, GADEKAR; SB, LOMATE; MA, SAKHARE (Innovare Journal of Sciences, 2020)
Objective: Scolecite is naturally occurring zeolite, Which contain alumina and silica in the structure. Herein we report, scolecite as an efficient and reusable catalyst for the synthesis of 2-amino-4H-chromenes from three component condensation of aromatic aldehydes, malononitrile and alpha or beta naphthol in ethanol. Materials and Method: Solvents used were of analytical and laboratory grade. The product were prepared by reflux method and analyzed by melting points, TLC, 1H-NMR, IR and Mass spectroscopy. Results: 2-amino-4H-chromenes synthesized successfully using scolecite as catalyst. The lewis acidic and basic sites of the scolecite enhance the rate of reaction. The electron donating and electron withdrawing group gives similar yield of products. Conclusion: This methods offers simple, clean, fast, efficient and reusability of catalyst for the synthesis of 2-amino-4H-chromenes. Which overall contribute to the green chemistry.